SEBUAH TINJAUAN ANTARA PENGEMBANGAN POLA PEMUKIMAN DAN PENGELOLAAN SEMPADAN SUNGAI - Nurfansyah Nurfansyah; Novitasari Novitasari (INFO-TEKNIK, 2006)
Town of Banjarmasin passed by many great rivers and small have very big potency to be developed on the other side facing problems in urban design which not yet been managed as town base on river potency. Intention of this research is to know influence of pattern architectural settlement of area related to regulation of water resources management at river borderThe aim of this research is special attention at river border society characteristic, settlement pattern and water resources at river side. Besides development of river border area destined as society interaction center or place in this time, need is also thought of by how development of have continuation, hence needed more comprehensive study to dot center development of river border and can be made reference for local government in determining wisdom development of better river border area.